2003
DOI: 10.1074/jbc.m207888200
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression and Characterization of Mouse Spermine Oxidase

Abstract: Polyamine oxidases are key enzymes responsible of the polyamine interconversion metabolism in animal cells. Recently, a novel enzyme belonging to this class of enzymes has been characterized for its capability to oxidize preferentially spermine and designated as spermine oxidase. This is a flavin adenine dinucleotidecontaining enzyme, and it has been expressed both in vitro and in vivo systems. The primary structure of mouse spermine oxidase (mSMO) was deduced from a cDNA clone (Image Clone 264769) recovered b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 36 publications
(41 reference statements)
2
82
0
Order By: Relevance
“…On the other hand, mammalian PAOs are involved in a PA back-conversion pathway (Vujcic et al 2003;Wu et al 2003). In addition, mammalian Spm oxidase converts Spm to Spd along with the production of 3-aminopropanal and H 2 O 2 without the acetylation process (Wang et al 2001;Vujcic et al 2002;Cervelli et al 2003;Seiler 2004). Even in plant, PA back-conversion activity was reported for AtPAO1, an isoform of five Arabidopsis PAOs ).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…On the other hand, mammalian PAOs are involved in a PA back-conversion pathway (Vujcic et al 2003;Wu et al 2003). In addition, mammalian Spm oxidase converts Spm to Spd along with the production of 3-aminopropanal and H 2 O 2 without the acetylation process (Wang et al 2001;Vujcic et al 2002;Cervelli et al 2003;Seiler 2004). Even in plant, PA back-conversion activity was reported for AtPAO1, an isoform of five Arabidopsis PAOs ).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The recombinant APAO and SMO proteins were expressed in E. coli BL21 DE3 cells and purified as previously reported by Bianchi et al 20 and Cervelli et al, 11 respectively. SDS/ PAGE electrophoretic analysis was performed on purified recombinant proteins to assess the grade of purity.…”
Section: Expression and Purification Of Apao And Smo Proteins In E Cmentioning
confidence: 99%
“…At present, only the three-dimensional structures of two members of the polyamine oxidase family are available, namely the maize polyamine oxidase (ZmPAO 17,18 ) and the yeast polyamine oxidase (FMS1 19 ). Molecular modeling of mouse SMO based on the three-dimensional structure of ZmPAO and sequence analysis of animal polyamine oxidases indicated that the general features of the ZmPAO threedimensional structure are conserved in the mammalian enzymes 11,20,21 . Furthermore, molecular modeling, docking and site-directed mutagenesis studies demonstrated that Spm binds to mammalian SMO in the same fashion as observed in the yeast FMS1, which shares with SMO and APAO the substrate oxidation mode 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Active splice variants are found both in the cytoplasm and the nucleus. [16][17][18] The predominant human splice variant, SMO1 (SMO/PAOh1), codes for a 61 kD protein containing 555 amino acids.…”
mentioning
confidence: 99%